The role of p63 proteins in tumorigenesis and the significance of their expression in the diagnosis of skin and female genital tract neoplasms - Wysocka-Dubielecka, Kalina M.; Majewski, Sławomir; Łoza, Katarzyna (Dermatology Review/Przegląd Dermatologiczny, 2015)
p63 proteins are p53 homologs, and with p73 belong to the p53 family. These transcription factors regulate metabolism, proliferation, differentiation, aging and cell death. p63 is crucial for development and maintenance of squamous epithelium, and plays an important role in cancerogenesis. p63 exists in multiple isoforms belonging to 2 main groups: TAp63 and ΔNp63. TAp63 are expressed at very low levels (except for oocytes). ΔNp63 isoforms are predominant isoforms overexpressed in basal epithelial cells of skin, appendages, breast, prostate, and urinary tract. In contrast to TAp63, they are believed to act as oncoproteins. In the female genital tract p63 may be a very useful marker for distinguishing problematic cancers, when diagnosis determines the therapeutic management. It seems that p63 is necessary for activation of HPV late gene expression upon epithelial proliferation and differentiation. p63 is increasingly being taken into account in the diagnosis of epithelial tumors of skin, genital tract, breast, head, neck and lungs.